Variation in lion population densities across the Greater Kafue Ecosystem, Zambia: Lessons for landscape‐scale monitoring - Paolo Strampelli; Xia Stevens; Will Donald; Davies Bubala; Lucky Mulenga; Mutakatala Kaponde; Blessing Samalesu; Edwin Phiri; Nelly Phiri; Bwalya Andrew Mulenga; Twakundine Simpamba; Adrian Kaluka; et al. (Ecological Solutions and Evidence, 2025)
Abstract The Greater Kafue Ecosystem (GKE) is a large protected area complex in Zambia, spanning over 65,000 km2. It comprises Kafue National Park (KNP, measuring over 22,000 km2) and nine surrounding community‐managed Game Management Areas (GMAs). The GKE is considered a stronghold for the African lion (Panthera leo), a charismatic species of high conservation value. Although landscape‐scale monitoring of wildlife populations is essential for their effective conservation management, until now most research and monitoring of lion populations in large landscapes such as the GKE has taken place in a few highly studied areas of study landscapes, hindering the adoption of an ecosystem‐scale approach for the management of lion populations. In the GKE, this is further compounded by the area primarily comprising miombo woodlands and including trophy hunting areas, both of which are understudied across the species' range. We carried out 12 camera trap‐based spatially explicit capture–recapture (SECR) surveys aimed at estimating lion population density across the GKE, overall sampling approximately 12,174 km2 of lion habitat (c. 27% of available lion habitat in the GKE). Our surveys resulted in 3903 photographs of lions, which were used to identify 185 individuals over 1 year of age. Relative to lion densities estimated using comparable methods elsewhere, densities across the GKE were low to moderate at most sites, ranging from 0.23 lions >1 year per 100 km2 (SE: 0.15, 95% CI: 0.07–0.74) in Mulobezi GMA to 5.10 lions >1 year of age per 100 km2 (SE: 0.73, 95% CI: 3.86–6.73) in a productive and well‐protected area of central KNP. We argue that the relatively low population densities at most sites are likely a result of low prey availability—itself a consequence of both anthropogenically induced factors (primarily bushmeat poaching) and naturally low productivity of dystrophic miombo woodlands—and direct anthropogenic mortality of lions. Practical Implication: Our study provides some of the first landscape‐scale, spatially explicit insights into variation in lion densities across miombo woodlands and sustainable use landscapes, as well as providing baselines for future monitoring for this globally important lion population. Finally, we present methodological practical insights and recommendations relating to camera trap‐based SECR lion population monitoring.